An In Situ Formed Surface Coating Layer Enabling LiCoO2 with Stable 4.6 V High‐Voltage Cycle Performances - Wang, Yi; Zhang, Qinghua; Xue, Zhi‐Chen; Yang, Lufeng; Wang, Junyang; Meng, Fanqi; Li, Qinghao; Pan, Hongyi; Zhang, Jie‐Nan; Jiang, Zheng; Yang, Wanli; Yu, Xiqian; et al. (Advanced energy materials, 2020)
The development of high‐voltage LiCoO2 is essential for achieving lithium‐ion batteries with high volumetric energy density, however, it faces a great deal of challenges owing to the materials, structure and interfacial instability issues. In this work, a strategy is developed, through heat annealing a precoated surface layer to in situ form a high‐voltage‐stable surface coating layer, which is demonstrated to be highly effective to improve the high‐voltage performance of LiCoO2. It is discovered that LiCoO2 reacts with Li1.5Al0.5Ti1.5(PO4)3 (LATP) at 700 °C to form exclusively spinel phases in addition to Li3PO4, which are structurally coherent to the layered lattice of LiCoO2. The heat annealing of the precoated thin layer of LATP enables the formation of a high‐quality surface layer. Spinel phases possess high‐voltage‐stable structures with much weaker oxidizing ability of lattice oxygen than layered structure. In addition, the Li3PO4 is a good lithium‐ion conductor with excellent chemical stability at high voltages. All these benefits contribute to the construction of a uniform and conformal high‐voltage‐stable surface layer with favorable lithium conducting kinetics at the LiCoO2 surface. The modified LiCoO2 shows excellent 4.6 V high‐voltage cycle performance at both room temperature and 45 °C. The thermal stability is greatly enhanced as well. In situ construction of a high‐voltage‐stable surface coating layer on the LiCoO2 surface is achieved by heat annealing the precoated Li1.5Al0.5Ti1.5(PO4)3 surface layer. The surface‐modified LiCoO2 shows superior 4.6 V high‐voltage cycle performances at both room temperature and 45 °C. The thermal stability of the modified sample is enhanced as well.